Estudo psiquiátrico forense sobre 130 pacientes internados em hospital de custódia e tratamento - Ceará - Dummar Filho, João (2004)
ABSTRACT Objective: Evaluate ,the profile of the clients at the Governor Stenio Gomes Psychiatry Institute from 01/01/2003 to 08/30/2003 Method: Retrospective evaluation of medicai prontuário and interviews with the hospitalized patients. Results: The social-demographic data (n=130) show us a high percentage of the illiterate (35.4%) and individuais who haven’t completed the basic schooling (41.5%). Regarding to professional qualification, we notice significant percentage of patients with no profession (28.5%) and patients with weak professional qualification (50.7%). In the second phase of the research (n=81), we notice that 28.4% of the patients had schizophrinia; 25.9 were hospitalized due to Chemical dependence; 16.0 had unspecified psychoses; and 12.3% were patients with personality disorders. In light of the articles from the Criminal Code, we notice that 46.9% of the patients were charged with Homicides (art. 121) ; 18.5% charged with body injury(art. 129) ; 9.8% charged with pick-pocketing (art. 155) and 8.6% charged with robbery. By analyzing the data collected, we have come to see that 24 cases of homicides and 7 cases of body injuries were committed against close relatives. Conclusions: 1) Through the statistical evaluation of the social-demographic data, we have noticed high percentage of illiterate patients who haven’t finished up the basic schooling with no profession or with weak professional qualification. 2) these data in addition to the conceptions provoked by the disease e by the criminality indicate that these patients will have few chances of joining back the work market and difficulties of socio-family adjustments. In the evaluation of the analyses, we have come to see an elevate incidence of homicide and/or body injuries committed against close relatives, provoking a severe impact under the nucleus of these patients’ families. In these specific cases, family rejection against the sick person is very likely to happen, which contributes to increase the number, which is already high, of the chronic patients hospitalized in the Governor Stenio Gomes Psychiatry Institute. 3) In the study of the clinicai cases, we have seen that the launch of the psychotic crisis causes perplexity and doubts in the family about the procedures to be taken. This factor alongside with of the deficiencies found in the public psychiatric medicai Service may bring about damages to the patients and theis family members. In three out of four clinicai cases studied, it was found that the association of severe psychoses with the abusive use of drugs and alcohols which preceded the violent behavior of the patient. It is recommended that in cases like that, that a detailed psychiatric Anamnese and immediate medicai procedures, giving special attention to those psychotic patient cases with precedents of violent behavior, a not continued treatment and use of alcohol and illegal drugs. Thus, we can make ana effective secondary prevention, avoiding criminal consequences such as those that happened among the patients that are doing time at IPGSG.